Cognição e significatividade no discurso político - Brito, Maria do Espirito Santo (2015)
This study has as its central object of inquiry the construction of meaningfulness in Dilma Rousseff e José Serra’s electoral discourse from the 2010 political campaign for the nation presidency. Starting with the principles that mind determines the way of understanding reality providing imaginative thinking and that the meaningfulness has consequences for the experience we have proposed to investigate how electoral discourse conceptualization is oriented to the achievement of their persuasion goals and how it can influence an electoral campaign outcome. To elucidate our assumptions we have used data from the televised electoral publicity of each candidate conveyed by internet and recorded in cds for interpretative analysis. This development has been endorsed by the Cognitive Linguistics theoretical principles mainly those from Experiencialism taking in account the sociocognitive aspects of used language, the embodiment and imagination notions as well as by Turner and Fauconnier’s theory on mental spaces in discourse commonly accepted as a tool for analysis of discourse interpretations or as a cognition and conceptualization theory. According to the results the ability for conceptual integrations turns language into an advanced human activity, that is, a manifestation of the hidden cognitive construction highly abstract and imaginative; the underlying mental processes are the basis for the political-electoral discourse building the political discourse meaningfulness due to the persuasion therefore due to their consequences for the experience.